Legal regime of mouthwashes with plant extracts in the european community - Suciu, Felicia; Roșca, Adrian Cosmin; Popescu, Antoanela; Stoicescu, Iuliana; Lupu, Carmen Elena; Badea, Victoria (Technium BioChemMed, 2023)
The mouthwashes in the Romanian legislation are not clearly included in the category of cosmetics, alimentary supplements or medicines. According to European legislation, the mouthwashes fall under Regulation (EC) No 1223/2009 of the European Parliament and of the Council of 30 November 2009 in the category of cosmetic products. Thus, on the Romanian and European market there are many cosmetic preparations in the form of mouthwashes that are notified as cosmetic products in the Cosmetics Notification Portal. Other products in the form of mouthwashes in general containing plant and animal extracts are approved and regulated as dietary supplements by the Institute of Food Bio resources, according to Order no. 244/2005, Order No. 1228/2005, Order No. 1946/2014, Law 491/2003, Annex to Order no. 244/2005 and Order 1069/2007 [1]. The ANMDMR (National Agency for Medicines and Medical Devices of Romania) has not approved on the Romanian market any medicine to be formulated in the form of a mouthwash to the EMA (European Medical Agency) which has regulated mouthwashes with active medicinal substances in the pharmaceutical form of mouthwashes.